Optimizing Eating Performance for Older Adults With Dementia Living in Long‐term Care: A Systematic Review. Issue 4 (29th June 2015) - Liu, Wen; Galik, Elizabeth; Boltz, Marie; Nahm, Eun‐Shim; Resnick, Barbara
ABSTRACT Background Review of research to date has been focusing on maintaining weight and nutrition with little attention on optimizing eating performance. Objective To evaluate the effectiveness of interventions on eating performance for older adults with dementia in long‐term care (LTC). Methods A systematic review was performed. Five databases including Pubmed, Medline (OVID), EBM Reviews (OVID), PsychINFO (OVID), and CINAHL (EBSCOHost) were searched between January 1980 and June 2014. Keywords included dementia, Alzheimer, feed(ing), eat(ing), mealtime(s), oral intake, autonomy, and intervention. Intervention studies that optimize eating performance and evaluate change of self‐feeding or eating performance among older adults (≥65 years) with dementia in LTC were eligible. Studies were screened by title and abstract, and full texts were reviewed for eligibility. Eligible studies were classified by intervention type. Study quality was accessed using the Quality Assessment Tool for Quantitative Studies, and level of evidence using the 2011 Oxford Centre for Evidence‐Based Medicine (OCEBM) Levels of Evidence. Results Eleven intervention studies (five randomized controlled trials [RCTs]) were identified, and classified into four types: training program, mealtime assistance, environmental modification, and multicomponent intervention. The quality of the 11 studies was generally moderate (four studies were rated as strong, four moderate, and three weak in quality), with the main threats as weak designs, lack of blinding and control for confounders, and inadequate psychometric evidence for measures. Training programs targeting older adults (Montessori methods and spaced retrieval) demonstrated good evidence in decreasing feeding difficulty. Mealtime assistance offered by nursing staff (e.g., verbal prompts and cues, positive reinforcement, appropriate praise and encouragement) also showed effectiveness in improving eating performance. Linking evidence to action This review provided preliminary support for using training and mealtime assistance to optimize eating performance for older adults with dementia in LTC. Future effectiveness studies may focus on training nursing caregivers as interventionists, lengthening intervention duration, and including residents with varying levels of cognitive impairment in diverse cultures. The effectiveness of training combined with mealtime assistance may also be tested to achieve better resident outcomes in eating performance.